HERMENEUTIC APPROACH AND ITS SIGNIFICANCE IN DEVELOPING KNOWLEDGE OF FUTURE HISTORY TEACHERS ABOUT THE LAWS OF THE HISTORICAL PROCESS (Scientific journal of the Fergana State University, 2024)
In this article, the effectiveness of future history teachers' knowledge development based on the hermeneutic-cognitive technology, hermeneutic-cognitive technology, and the hermeneutic approach is studied. Also, the hermeneutic approach and its importance in developing the knowledge of future history teachers about the laws of the historical process are analyzed..